Afiks Derivasi Per-/-An dalam Bahasa Indonesia: Tinjauan dari Perspektif Morfologi Derivasi dan Infleksi - Ermanto .; Emidar . (Fakultas Bahasa dan Seni UNP, 2011)
This article aims to reveal the affixation process using derivational affix per-/-an on Indonesian derived nouns based on the theory of derivational and inflectional morphology. This research was a qualitative research method by using the theory of structural linguistics and case grammar. The object of the research was a derivational affix per-/-an used on Indonesian derived nouns, and the data were sentences (utterances) whose nouns having the derivational affix per-/-an. The analysis method used was a distributional method. Viewed from the perspective of derivational and inflectional morphology, the affixation of the derivational affix per-/-an on the verbs (both base verbs and derived verbs) and on the noun can produce (1) behavioral nouns, (2) Action nouns, (3) actional instrumental nouns, (4) behavioral instrumental nouns, (5) behavioral locative noun, (6) process nouns, (7) collective nouns, (8) abstract nouns. Kata Kunci: